Starostne razlike in razlike med spoloma v agresivnosti slovenskih učencev in dijakov - Kozina, Ana (Psihološka obzorja (Ljubljana), 2012)
The study examined age and gender differences in aggression using three representative samples for Slovenia: 4th grade elementary school students; 8th grade elementary school students; 4th grade secondary school students in Matura programs. The results were based on the LA aggression scale that measures general aggression and four specific types of aggression: physical aggression (TA), verbal aggression (BA), internal aggression (NA) and aggression towards authority (AA). Based on the results of two-way ANOVA we found important effects of age, gender and their interaction. The gender differences were significant in the groups of elementary school students but not in secondary school students. Male elementary school students, 4th and 8th grade, were more aggressive compared to female elementary school students. 8th grade elementary school students were more physically, verbally, internally aggressive and more aggressive towards authority when compared to 4th grade elementary school students. Secondary school students were significantly less physically and verbally aggressive, and on the other hand more internally aggressive when compared to both groups of elementary school students. Secondary school students reported higher level of aggression towards authority than 4th grade elementary students, and lower level then 8th grade elementary students. The results were congruent with the findings of the research literature indicating higher aggression of males when compared to females and different developmental paths for different types of aggression in question. The study introduced important findings regarding age and gender differences in representative school samples in Slovenia and proposed future research mostly in direction of including measures of indirect aggression that is linked to female gender and older students.
Keywords: aggressiveness; agresivnost; gender differences; razlike med spoloma; starost; age differences; elementary school students; učenci; high school students; dijaki; Lestvica agresivnosti (LA)